Learning experiences in the teaching of mathematics to incarcerated university students: a humanistic sense - Castrillo Duarte, Óscar Mario (2014)
This paper brings together the experiences of research conducted with college students doing time at the Liberia Criminal Center, as support to the course of Mathematics for Administrators II of Universidad Estatal a Distancia (UNED). The problems they face are: lack of teaching resources, inadequate infrastructure, and lack of mentoring to provide them with meaningful learning. The commitment of the researcher was to provide support to the students in the course, through a participatory and humanistic methodology, oriented to the attainment of study techniques to enable them to acquire the necessary mathematical skills. From the humanist perspective, the learning possibilities of a student in prison were assessed, in relation to those of students who attend college.